Jedi public health: Co-creating an identity-safe culture to promote health equity. (December 2016) - Geronimus, Arline T.; James, Sherman A.; Destin, Mesmin; Graham, Louis F.; Hatzenbuehler, Mark L.; Murphy, Mary C.; Pearson, Jay A.; Omari, Amel; Thompson, J. Phillip
Abstract: The extent to which socially-assigned and culturally mediated social identity affects health depends on contingencies of social identity that vary across and within populations in day-to-day life. These contingencies are structurally rooted and health damaging inasmuch as they activate physiological stress responses. They also have adverse effects on cognition and emotion, undermining self-confidence and diminishing academic performance. This impact reduces opportunities for social mobility, while ensuring those who "beat the odds" pay a physical price for their positive efforts. Recent applications of social identity theory toward closing racial, ethnic, and gender academic achievement gaps through changing features of educational settings, rather than individual students, have proved fruitful. We sought to integrate this evidence with growing social epidemiological evidence that structurally-rooted biopsychosocial processes have population health effects. We explicate an emergent framework, Jedi Public Health (JPH). JPH focuses on changing features of settings in everyday life, rather than individuals, to promote population health equity, a high priority, yet, elusive national public health objective. We call for an expansion and, in some ways, a re-orienting of efforts to eliminate population health inequity. Policies and interventions to remove and replace discrediting cues in everyday settings hold promise for disrupting the repeated physiological stress process activation that fuels population health inequities with potentially wide application.